3(x2+1)=(x+2)2

Simple and best practice solution for 3(x2+1)=(x+2)2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x2+1)=(x+2)2 equation:



3(x2+1)=(x+2)2
We move all terms to the left:
3(x2+1)-((x+2)2)=0
We add all the numbers together, and all the variables
3(+x^2+1)-((x+2)2)=0
We multiply parentheses
3x^2-((x+2)2)+3=0
We calculate terms in parentheses: -((x+2)2), so:
(x+2)2
We multiply parentheses
2x+4
Back to the equation:
-(2x+4)
We get rid of parentheses
3x^2-2x-4+3=0
We add all the numbers together, and all the variables
3x^2-2x-1=0
a = 3; b = -2; c = -1;
Δ = b2-4ac
Δ = -22-4·3·(-1)
Δ = 16
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{16}=4$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-2)-4}{2*3}=\frac{-2}{6} =-1/3 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-2)+4}{2*3}=\frac{6}{6} =1 $

See similar equations:

| (3x-1)+13=6 | | 15+3x=26x+2 | | 3u−4=8 | | 11x-3x+6=6 | | -13=7x-1-4x | | 2x-4=8x-43 | | 4/2x=8/x+2 | | 3=-(4x+7)+3x | | 18=|6x+12|=-24 | | 8g+15=64 | | 5.2=a-0.45.2=a-0.4 | | 34+4n=28 | | 11(x-2)+7=5+x-20 | | 1-3(2x)=7 | | 9(-7w+5)=-48-63w | | (2x+8)+8x=12 | | 3x2+5x-2=2x-5 | | 25x+14x=175 | | (2x+3)^2=)3x-4)^2 | | 3.3−|3+x|=−2.4 | | (X)=5x-2 | | 4a/2=5 | | 8-3(w+13)=4(w+11)-7w | | 3(t-15)=12 | | (2x+8)+8x=16 | | 5x-(-2-x)=5 | | 5x-9-2-x)=5 | | 0.7x+0.6=0.9x-0.8 | | 1/3x+2=1/4 | | 3x+10+4x+5x-10=360 | | 3x-(4x+7)=0 | | 4x-1*2=2x+2*2x |

Equations solver categories